Biology, Ecology and Control of Ailanthus Defoliator Atteva fabriciella Swed. (Lepidoptera: Yponomeutidae) in Madhya Pradesh - Mathur, R. N.; Chatterjee, P. N.; Sen-sarma, P. K. (Indian Forester, 1970)
The present paper deals with the problem of Ailanthus defoliation in M.P. (Nimar Forest Division, Nepanagar) and gives briefiy an account of ecology and control measures of Alleva fabriciella Swed. (Lepidoptera: Yponomeutidae) the deloliator of Ailanthus excelsa.